Figuration, constructions and English phrasal verbs: The instances of come up - Tsaroucha Efthymia (ExELL (Explorations in English Language and Linguistics))
The paper investigates the evocation of the figurative meanings of English phrasal verbs of the form: component verb come + component particle up when they are employed in resultative constructions. Four instances of come up are discussed. It is suggested that the figurative meanings of come up are rooted to conceptual metaphors.